Pengaruh Ekonomi Terhadap Kdrt Dalam Rumah Tangga - Randi Putra Ramadhan (CV. ITTC INDONESIA, 2024)
Domestic Violence (DV) is a complex and multidimensional social issue influenced by various factors, one of which is economic conditions. This study aims to analyze the impact of economic factors on the prevalence of domestic violence within households. The research employs a qualitative approach, collecting data through interviews and literature review. The findings reveal that economic instability, unemployment, and poverty are significant driving forces behind the occurrence of domestic violence. Stress resulting from economic pressure often leads to conflicts within households, which can trigger violent actions. Additionally, cultural factors and social norms play a role in exacerbating domestic violence situations. This study concludes that to reduce domestic violence, efforts must be made to improve the economic conditions of communities and provide education on healthy relationships within households.